2022
DOI: 10.4103/jcrt.jcrt_174_21
|View full text |Cite
|
Sign up to set email alerts
|

The hemoglobin, albumin, lymphocyte, and platelet (HALP) score is a novel prognostic factor for patients with diffuse large B-cell lymphoma

Abstract: Context: The hemoglobin, albumin, lymphocyte, and platelet (HALP) score is a prognostic marker in several types of malignant tumors. The prognostic value of HALP score in diffuse large B-cell lymphoma (DLBCL) remains unknown. Aim: We aimed to determine the prognostic value of baseline HALP score in DLBCL patients. Subjects and Methods: We retrospectively analyzed data from 153 newly diagnosed DLBCL patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…In a 2021 study by Vlatka et al, the authors retrospectively queried 153 newly diagnosed diffuse large B-cell lymphoma patients receiving R-CHOP (Rituximab, Cyclophosphamide, Doxorubicin, Vincristine, and Prednisone) chemotherapy [ 80 ]. This study found that lower HALP was shown to be associated with unfavorable clinicopathological characteristics and a predictor of long term survival.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a 2021 study by Vlatka et al, the authors retrospectively queried 153 newly diagnosed diffuse large B-cell lymphoma patients receiving R-CHOP (Rituximab, Cyclophosphamide, Doxorubicin, Vincristine, and Prednisone) chemotherapy [ 80 ]. This study found that lower HALP was shown to be associated with unfavorable clinicopathological characteristics and a predictor of long term survival.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al, showed that low HALP was significantly associated with poor tumor differentiation and higher TNM staging in pancreatic cancer [ 60 ]. Vlatka et al, has demonstrated that diffuse large B-cell patients with higher HALP were more likely be Stage I/II while lower HALP scores predicted increased rate of TNM Stage III/IV [ 80 ]. Duran et al, found low HALP breast cancer patients were also more likely to have more advanced clinical stage at time of surgery [ 61 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hematologic tumors, low HALP is associated with adverse clinicopathological features of diffuse large B-cell lymphoma and appears to be an independent adverse prognostic factor for International Prognostic Index. 46 Besides, HALP score is a valuable prognostic marker for patients with multiple myeloma. 47 A retrospective study with 319 pharyngeal cancer patients including nasopharyngeal carcinoma, oropharyngeal carcinoma and hypopharyngeal carcinoma indicated that HALP score was an independent factor for OS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an elevated platelet count is considered as an inflammatory biomarker and reflects the inflammatory response in lymphoma patients. Furthermore, consumptive character of malignant lymphomas has significant impact on nutritional status and host immune system ( 16 ).…”
Section: Introductionmentioning
confidence: 99%